2016
DOI: 10.1371/journal.pone.0156571
|View full text |Cite
|
Sign up to set email alerts
|

Random Forests for Global and Regional Crop Yield Predictions

Abstract: Accurate predictions of crop yield are critical for developing effective agricultural and food policies at the regional and global scales. We evaluated a machine-learning method, Random Forests (RF), for its ability to predict crop yield responses to climate and biophysical variables at global and regional scales in wheat, maize, and potato in comparison with multiple linear regressions (MLR) serving as a benchmark. We used crop yield data from various sources and regions for model training and testing: 1) gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
277
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 476 publications
(289 citation statements)
references
References 41 publications
(43 reference statements)
11
277
0
1
Order By: Relevance
“…Figure 6 illustrates the average accuracy, sensitivity and specificity value of proposed method, which is superior compared to existing approaches. Averagely, the accuracy gap between the proposed and existing methods are 23.04%, 20.093%, 13.09%, 7.02% and 14.34% reduction in accuracy value associated to SOM-DNN, SOM-KNN, weighted-SOM-KNN, RF-MLR [17], and SOM-LVQ [18]. Similarly, the proposed method delivers better performance compared to the existing approaches in terms of sensitivity and specificity.…”
Section: Results Of Classification Evaluationmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure 6 illustrates the average accuracy, sensitivity and specificity value of proposed method, which is superior compared to existing approaches. Averagely, the accuracy gap between the proposed and existing methods are 23.04%, 20.093%, 13.09%, 7.02% and 14.34% reduction in accuracy value associated to SOM-DNN, SOM-KNN, weighted-SOM-KNN, RF-MLR [17], and SOM-LVQ [18]. Similarly, the proposed method delivers better performance compared to the existing approaches in terms of sensitivity and specificity.…”
Section: Results Of Classification Evaluationmentioning
confidence: 86%
“…Similarly, the 70% training and 30% testing of collected data delivers, 0.8319 of precision and 0.9 of recall. The graphical representation of precision and recall comparison is stated in the [17] evaluated a machine-learning method: RF for predicting crop yield responses to climate and biophysical variables at global and regional scales in wheat, maize, and potato in comparison with MLR serving as a benchmark. RF was found highly capable of predicting crop yields and outperformed MLR benchmarks in all performance statistics that were compared.…”
Section: Results Of Classification Evaluationmentioning
confidence: 99%
“…The calibration performance of RF models was shown in Figure 3. Compared with previous model calibration at county scale [7,11,41], the model calibration in this study was based on pixel scale, which could improve the performance of crop yield estimation model at finer resolution. No matter for maize or sunflower, the R 2 and adjusted R 2 of all RF models were between 0.80 and 0.90, and the difference between R 2 and adjusted R 2 was very small due to the number of calibration data (272 for maize and 432 for sunflower) was far more than the number of predictors, which indicated that there was no over fitting phenomenon in our calibrated models.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used RF regression function implemented in the “Random Forest” package within Matlab R2017b software developed by MathWorks (Natick, MA, USA) to estimate the crop yield. Using remote sensing data as inputs, RF regression algorithm has been successfully applied to crop yield estimation in recent years [7,41,42]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation